Overhead Chop Exercise and Double Leg Balance Exercise on Postural Control Children With Autism Spectrum Disorder - Oktarina, Mona; Adinda Larasati Hapsari (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
This study aims to description of overhead chop exercises and double leg balance exercises in improving postural control to children with autism spectrum disorder (ASD). Method: This research is a qualitative descriptive research with a case study approach, type of action research. The samples were child patients who underwent therapy at the YCHI Autism Center clinic, South Tangerang. Overhead chop training provides an illustration of improving postural control in the sample. The sample is directed to receive proprioceptive stimulation which is then carried to the brain so that it can maintain an upright position and not fall. The double leg balance exercise also provides an illustration of improving postovertural control. The sample provides instructions for performing lift and chop movements. This movement forms a diagonal movement pattern which can help to rotate the trunk diagonally and stretch the thorax and pelvis. Overhead chop exercises and double leg balance exercises can provide overview of postural control in children with ASD.